So conceived and so dedicated : intellectual life in the Civil War-era north - Wongsrichanalai, Kanisorn; Foote, Lorien, 1969- (North's Civil War., 2015)
Highlighting recent and new directions in contemporary research in the field, So Conceived and So Dedicated offers a complete and updated picture of intellectual life in the Civil War-era Union. Compiling essays from both established and young historians, this volume addresses the role intellectuals played in framing the conflict and implementing their vision of a victorious Union. Broadly defining ""intellectuals"" to encompass doctors, lawyers, sketch artists, college professors, health reformers, and religious leaders, the essays address how these thinkers disseminated their ideas, sometime.